The Return of Repressed in Novel The Midnight Library (2020) by Matt Haig. - Rafiyan, Rayhan; Wahyuni, Delvi (Universitas Negeri Padang, 2024)
This research is an analysis of novel The Midnight Library by Matt Haig (2020). The design of this research is qualitative descriptive analysis. The analysis delves into the form of repression in the experience of Nora Seed. It enhances the analysis process by assisting in the unveiling of the meaning. The research used psychoanalysis theory by Sigmund Freud. The data in this research was obtained from the novel The Midnight Library by Matt Haig (2020), Based on the use of quotations from character, plot, and setting from the novel. The results show that there are two form of return of repression in the main character Nora Seed, consist of dream and anxiety. Furthermore, the data found from the novel shows Nora has released her repressed emotion by accepting her failure , Tolerancing the negative emotions, forgiving her parents in fact her parents are full of love to her, realizing that life is full of trials and needing connection to humans.